Solution of the Rayleigh-Plesset Equation Through the Finite Element Method (2013)
In this work we present numerical solutions of the Rayleigh-Plesset equation which describes the evolution of cavitating bubbles. In order to do that, we consider FEMG (Finite Element Method Galerkin); this simulation is performed for an inviscid and incompressible fluid in an uniform temperature field with constant surface tension, and the cavitation model into the which the pressure inside bubbles is equal to the fluid vapor pressure. Thus, in this problem is considered the Dirichlet boundary problem, and we obtained criteria for the boundary conditions at the cavitation phenomenon through to the which give rise to the bubble growing.